2012
DOI: 10.3857/roj.2012.30.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation of recurrent esophageal cancer after primary definitive radiotherapy

Abstract: PurposeFor recurrent esophageal cancer after primary definitive radiotherapy, no general treatment guidelines are available. We evaluated the toxicities and clinical outcomes of re-irradiation (re-RT) for recurrent esophageal cancer.Materials and MethodsWe analyzed 10 patients with recurrent esophageal cancer treated with re-RT after primary definitive radiotherapy. The median time interval between primary radiotherapy and re-RT was 15.6 months (range, 4.8 to 36.4 months). The total dose of primary radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…The study found that re-RT could improve survival rate of patients, but the incidence of EF was as high as 20% (11/55). Kim et al [30] retrospectively analyzed that 17 patients with recurrent EC were treated with re-RT after primary RT. EF occurred in 3 patients (17.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that re-RT could improve survival rate of patients, but the incidence of EF was as high as 20% (11/55). Kim et al [30] retrospectively analyzed that 17 patients with recurrent EC were treated with re-RT after primary RT. EF occurred in 3 patients (17.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation pneumonitis grade ≥3 was observed in 5.45%, and esophageal fistula/perforation was observed in 20.0% of the cases. Fakhrian et al reported on 54 patients with recurrent esophageal carcinoma undergoing salvage radiotherapy (14). Median survival time was 12 months (95% confidence interval: 7-17 months) and toxicity was in an acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients have recurrence or metastasis within 2 years after radiotherapy [4,7,8]. Without active intervention, the survival and prognosis of patients with disease progression are often poor, and most die within 1 year [9]. Although many researchers are actively exploring the best salvage treatment for LRESCC, there is still no consensus.…”
Section: Discussionmentioning
confidence: 99%